Standards and competencies of the EU - the market strategies of financial services in the Balkan region - Vignjevic Djordjevic, Nada (Journal of Applied Engineering Science, 2016)
New members joining the European Union, happily coincided with the economic rise worldwide. The investment industry has positioned itself at the time of European expansion in the emerging markets. Extended European capital market, preceded by a long period of preparation of the new members, in which they felt the positive effects of connecting with more mature markets. Experts point out that the World Bank policymakers eight new members of the European. Union should adopt a proactive stance in taking further financial reforms and that in addition to the rapid growth of the banking system and stimulate growth in the form of non-banking financial operations. Increasingly important shareholders associated with the strengthening power of institutional investors. So stockholding strengthened with the help of representatives of institutions in the field of insurance, pension funds and investment funds. All the major part of savings managed by institutional investors. Savings realized the benefits of financial innovation, which have significantly lowered the cost of the invested money management services and improve the quality and diversity of investments. This "gathering" individual savings, have improved the efficiency frontier relations income-risk and on the other hand, over-sized achieve the economies of scale transactions. Also, depositors can expect a higher level of revenues for the same level of risk.